Suitability and Carrying Capacity of Coastal Ecotourism in Clungup Mangrove Conservation (CMC), Malang District, East Java - Prasasti Aditya Dharma; Fredinan Yulianda; Gatot Yulianto (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
This study aims to determine the suitability and carrying capacity of coastal areas in the Clungup Mangrove Conservation (CMC) Malang Regency, East Java for coastal tourism activities such as beach recreation, mangrove tourism, snorkeling, and fishing. This research was conducted from August to October 2020 through a survey with an observative approach to obtain primary data, while secondary data was obtained from area managers as supporting data. The carrying capacity of the area for beach tourism activities is 3,234 people/day, mangrove tourism is 6,675 people/day, diving tours are 684 people/day, and snorkeling is 59 people/day. As for fishing activities, this area can accommodate 553 people/day, Canoeing 20,025 people/day, and camping 120 people/day. The number of tourists in the CMC area is still below its carrying capacity. The management of the number of tourists that are currently controlled is considered appropriate and follows the carrying capacity of the environment. However, the potential for the area to be developed closer to its carrying capacity is still possible. Increased tourist visits will provide economic benefits for the community and business actors who support tourism around the CMC area, causing an economic multiplier effect.